Fundamentals of geoenvironmental engineering understanding soil, water, and pollutant interaction and transport - Mohamed, Abdel-Mohsen Onsy; Paleologos, Evan K. (Butterworth-Heinemann, 2018)
Fundamentals of Geoenvironmental Engineering: Understanding Soil, Water, and Pollutant Interaction and Transport examines soil-water-pollutant interaction, including physico-chemical processes that occur when soil is exposed to various contaminants. Soil characteristics relevant to remedial techniques are explored, providing foundations for the correct process selection. Built upon the authors' extensive experience in research and practice, the book updates and expands the content to include current processes and pollutants. The book discusses propagation of soil pollution and soil characteristics relevant to remedial techniques. Practicing geotechnical and environmental engineers can apply the theory and case studies in the book directly to current projects. The book first discusses the stages of economic development and their connections to the sustainability of the environment. Subsequent chapters cover waste and its management, soil systems, soil-water and soil-pollutant interactions, subsurface transport of pollutants, role of groundwater, nano-, micro- and biologic pollutants, soil characteristics that impact pollution diffusion, and potential remediation processes like mechanical, electric, magnetic, hydraulic and dielectric permittivity of soils.--Provided by publisher.